The popular culture of the cold war: the spy genre and its evolution in the soviet cinema - Sukovataya, Viktoria (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2016)
The article is devoted to analyses of the cultural consciousness during the Cold War, which was reflected in the genre of spy cinema. It was argued that the spy movie (along with the film noir and nuclear fantasies) was one of the most representative genre of the Cold War, because it reflected the basic cultural notions of that epoch. It was concluded that the popular culture during the Cold War was focused on the genre of the spy detectives because it contains the most representative images of the confrontation between the Soviet and the Western societies